The Role of Islamic Religious Education Teachers in Shaping the Character of Students Who are Obedient in Praying at the Metuk 1 Mojosongo Boyolali State Elementary School - Asih Susanti; Siti Rohimah (Didaktika: Jurnal Kependidikan, 2024)
The aim of this research is to find out in depth the role of Islamic religious education teachers in forming the character of students who are obedient in praying. This research is qualitative research. The subjects of this research were teachers and students at the Metuk 1 Boyolali state elementary school. The instruments in this research were the school principal, Islamic religious education teacher and students. Data was taken through observation, interviews and documentation. Meanwhile, data analysis uses data reduction, data presentation and drawing conclusions. The results show that the role of teachers as teachers, motivators and supervisors is in forming the character of students who obey prayer. Meanwhile, the supporting factor is the support of representative teachers and prayer rooms. The inhibiting factors are the lack of student awareness regarding prayer observance, limited PAI learning time allocation and limited Islamic religious education teachers.